De Aalstenaar Nicolaus Stopius (c. 1516-Venetië 1570) en de Annoni in Dienst van Andreas Vesalius - Biesbrouck, Maurits; Goddeeris, Theodoor; Steeno, Omer (In Monte Artium, 2021)
Abstract Most authors discussing the persons helping Vesalius to prepare the transport of his manuscript with the wood-blocks for the plates for his De humani corporis fabrica libri septem to Oporinus, his printer in Basel, experience difficulties identifying them. Here is a tentative to present those assisting him with this task : Nicolaus Stopius, business agent of the printing house van Bomberghen and the merchants from Milan, the Danoni, as he called them.